Development of a 4wd prime mover With front mounted sprayer unit for circle spraying of immature oil palms - El Pebrian, Darius; Yahya, Azmi (2008)
A mechanized system for circle spraying palms of less than 3 years old has been developed for the oil palm plantation industry in Malaysia. This circle spraying is being carried out to every individual palms along the row and again repeated to every individual rows that are available within the field lot to be sprayed. Spraying at each individual palms is done at 1 meter radius from the palm center. A special single chassis 4WD multipurpose prime mover with a front mounted sprayer unit has been developed to mechanize this circle spraying operation. The prime mover runs on a 50.7 kW @ 2600 rpm KUBOTA V3300 water cooled diesel engine and equips with a Sauer Danfoss MPV46 axial piston pump with 210 bar maximum pressure @ 46 cm3 per revolution, oscillating front and rear axles, and 12-16.5 tires with the rear tires having opposite turning direction to the front tires. Such a design configuration would provide the required traction and maneuverability for the machine system in the undulating terrain conditions. The spraying unit on the prime mover consists of a hexagonal curved boom mounted at the front of the prime mover, a 600 liters capacity polyethylene cylindrical tank at the rear, a 12V electrical SHURFLO 8000 series pump with 6.9 bar maximum operating pressure @ 6.8 liters per minutes flow, and the associated hydraulic system for the raising, lowering, opening and closing of the boom. The hexagonal curved boom is made into two equal halves frame with a hinge mechanism at the frame rear ends to facilitate for its openings and closings. Six SCX2 RB solid cone nozzles are arranged on the hexagonal curved boom structure to give a 72.5 cm equal spacing between nozzles. Both laboratory and field tests have been conducted to determine the machine traveled speed range with slippage and without slippage, the individual nozzle flow uniformity and the complete spraying pattern. Without any doubts, this mechanized system has great potential to replace the current manual method using knapsack sprayer or motorized blower for circle spraying of immature palm trees or any immature fruit trees in large scale planting. The 4WD prime mover has been designed to be used with other relevant machine attachments for seedling planting, fertilizer application, in-field collection-transportation of fresh fruit bunches and in-field collection-transportation of loose fruits for the oil palm plantation industry